The frequency of significant relationships of selected features describing feet with the torso features among youth aged 7-13 - Kamil Rzadkowski; Mirosław Mrozkowiak (Kazimierz Wielki University, 2023)
Introduction. Research on the relationships and co-occurrence of the feet and torso features in a group of 4-6-year-old children showed that the values of the left foot features show a significantly more frequent relationship with the features of the torso than the right foot features. Material and method. The research was carried out in the group of adolescents aged 7 to 13 and registered 12,898 observations of the value of 90 features describing torso and feet. The working stand for measuring the features of body posture and feet using the photogrammetric method consists of a computer and a card, a programme, a monitor, a printer, and a projection-receiving device with a camera for measuring selected features. Conclusions • A similar number of features of the right and left foot is often associated with the torso features. The following features like width of the feet, the angle of the 5thhallux valgus and the left foot big toe, the heel angle and height of the right foot second arch, the height of the second longitudinal arch and the length of the left foot, and the length of the first arch of the right foot show especially frequent relationships. • The feet features show the most frequent significant relationship with the torso features of the frontal plane, whereas less of sagittal plane and occasionally of transversal plane. Torso features, which the most common features of the feet are significantly related to are the height and length of lumbar lordosis, the height of thoracic kyphosis, the angle of the torso flexion in the sagittal plane, the length of the thoracic kyphosis, the bent angle of the thoracic-lumbar spine, the depth of thoracic kyphosis, the depth of lumbar lordosis, and the inclination angle of the upper thoracic segment of the spine. The features of the feet are whereby most frequently related to the features of lumbar lordosis.